Structural characterization of dissolved organic matter in permafrost peatland lakes - Folhas, Diogo (2020)
Thermokarst lakes result from the thawing of ice-rich permafrost and are widespread across northern landscapes. These waters are strong emitters of methane, especially in permafrost peatland regions, where they are stained black by high concentrations of dissolved organic matter (DOM). In the present study, we aimed to structurally characterize the DOM from a set of peatland thermokarst lakes that are known to be intense sites of microbial decomposition and methane emission. Samples were collected at different depths from three thermokarst lakes in the Sasapimakwananisikw (SAS) River valley near the eastern Hudson Bay community of Kuujjuarapik–Whapmagoostui (Nunavik, Canada). Samples were analyzed by spectrofluorometry, Fourier-transform infrared spectroscopy (FTIR), nuclear magnetic resonance spectroscopy (NMR), and elemental analysis. Fluorescence analyses indicated considerable amounts of autochthonous DOM in the surface waters of one of SAS 1A, indicating a strong bioavailability of labile DOM, and consequently a greater methanogenic potential. The three lakes differed in their chemical composition and diversity, suggesting various DOM transformations phenomena. The usefulness of complementary analytical approaches to characterize the complex mixture of DOM in permafrost peatland waters cannot be overlooked, representing a first step towards greater comprehension of the organic geochemical properties of these permafrost-derived systems